Pembuatan Totebag Berbahan Dasar Kain Sisa Hasil Produksi Dengan Memanfaatkan Tukang Jahit Keliling Guna Meningkatkan Perekonomian Masyarakat Kota Solo - Gracia Angelita Suryawan (Pengelola Jurnal Politeknik Negeri Ketapang, 2021)
Poverty is one of the problems that often arise in various cities and even countries. Especially in this era of the Covid-19 pandemic. It is undeniable that this pandemic has resulted in a decline in the economy in Indonesia, especially in the city of Solo. The city of Solo is one of the cultural cities that has the potential for Batik as one of the icons of this city. Not only the potential of craft resources, the potential of human resources, which is often called craftsmen, is also widely found in this city. One of them is the itinerant tailor who goes around every day from one complex to another to help sew the clothes of the local residents. However, with the impact of COVID-19, many itinerant tailors have started to lose their jobs and have a negative impact on their economic growth. This has a negative impact on the sustainable development goals in point 8 regarding decent work and economic growth. In this paper, we use the Design Thinking method which aims to help improve the economy of the people in the city of Solo and also increase the potential of human resources through itinerant tailors who are our partners in processing the waste of the remaining batik cloth produced into a tote bag with a beautiful and elegant design. modern